Pengembangan E-LKPD Berbasis Open-ended Berbantuan Liveworksheets pada Materi Segiempat dan Segitiga untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas VII MTs - Mubarrok, Azimatul; Wahyuni, Fina Tri (Education Mind Based Development Association, 2023)
Efforts to improve students' creative thinking skills can be done in several ways, one of which is through the development of teaching materials in the form of an open-ended based E-LKPD. The purpose of this study was to find out the process of developing open-ended based E-LKPD, to find out the feasibility and practicality of open-ended based E-LKPD, and to find out students' creative thinking skills after using open-ended based E-LKPD. The results of this study indicate that: (1) The development of teaching materials in the form of an open-ended based E-LKPD assisted by liveworksheets in the process uses the ADDIE development model namely analyze, design, development, implementation, and evaluation stages. (2) The resulting E-LKPD is categorized as feasible, with an average percentage of 85.5%. (3) The practicality of the E-LKPD is obtained from a user response questionnaire, obtaining a total percentage of all aspects of 81% with very practical criteria. (4) Students' ability to think creatively after participating in learning using the developed open-ended based E-LKPD is in the creative category.